Greater history of traumatic event exposure and PTSD associated with comorbid body dysmorphic disorder in a large OCD cohort. (July 2020) - Valderrama, Jorge; Hansen, Stella Kim; Pato, Carlos; Phillips, Katharine; Knowles, James; Pato, Michele T.
Highlights: We examine trauma, PTSD, OCD, and OCD with comorbid BDD. OCD + comorbid BDD associated with higher rates of at least one traumatic life event. OCD and comorbid BDD associated with PTSD more than OCD without BDD. Abstract: The present study examined whether or not there are differential rates of traumatic event exposure and presumed Post-Traumatic Stress Disorder (PTSD) between individuals with OCD without comorbid presumed BDD (OCD-Non-BDD) and individuals with OCD with comorbid presumed BDD (OCD+BDD) within a large cohort of OCD participants ( N  = 605). Individuals in the OCD+BDD group had significantly higher rates of endorsing at least one lifetime traumatic event and presumed PTSD than individuals with OCD-Non-BDD. Additionally, individuals in the OCD+BDD group with comorbid presumed PTSD had significantly higher rates of major depressive disorder (MDD) and presumed panic disorder (PD). A logistic regression analysis revealed that presumed PTSD significantly predicted the presence of BDD symptoms among individuals who experienced at least one lifetime traumatic event in our sample. These findings suggest that individuals in the OCD+BDD group were more likely to have experienced a traumatic event in their lives, to experience presumed PTSD, and to have MDD and presumed PD than individuals in the OCD-Non-BDD group. Clinical implications and possible mechanistic pathways from trauma exposure to OCD and BDD symptomatology are discussed.